FACT, the Bur Kinase Pathway, and the Histone Co-Repressor HirC Have Overlapping Nucleosome-Related Roles in Yeast Transcription Elongation - Stevens, Jennifer R. (Public Library of Science, 2011)
Gene transcription is constrained by the nucleosomal nature of chromosomal DNA. This nucleosomal barrier is modulated by FACT, a conserved histone-binding heterodimer. FACT mediates transcription-linked nucleosome disassembly and also nucleosome reassembly in the wake of the RNA polymerase II transcription complex, and in this way maintains the repression of ‘cryptic’ promoters found within some genes. Here we focus on a novel mutant version of the yeast FACT subunit Spt16 that supplies essential Spt16 activities but impairs transcription-linked nucleosome reassembly in dominant fashion. This Spt16 mutant protein also has genetic effects that are recessive, which we used to show that certain Spt16 activities collaborate with histone acetylation and the activities of a Bur-kinase/Spt4–Spt5/Paf1C pathway that facilitate transcription elongation. These collaborating activities were opposed by the actions of Rpd3S, a histone deacetylase that restores a repressive chromatin environment in a transcription-linked manner. Spt16 activity paralleling that of HirC, a co-repressor of histone gene expression, was also found to be opposed by Rpd3S. Our findings suggest that Spt16, the Bur/Spt4–Spt5/Paf1C pathway, and normal histone abundance and/or stoichiometry, in mutually cooperative fashion, facilitate nucleosome disassembly during transcription elongation. The recessive nature of these effects of the mutant Spt16 protein on transcription-linked nucleosome disassembly, contrasted to its dominant negative effect on transcription-linked nucleosome reassembly, indicate that mutant FACT harbouring the mutant Spt16 protein competes poorly with normal FACT at the stage of transcription-linked nucleosome disassembly, but effectively with normal FACT for transcription-linked nucleosome reassembly. This functional difference is consistent with the idea that FACT association with the transcription elongation complex depends on nucleosome disassembly, and that the same FACT molecule that associates with an elongation complex through nucleosome disassembly is retained for reassembly of the same nucleosome.